2020
DOI: 10.3390/coatings10040378
|View full text |Cite
|
Sign up to set email alerts
|

GLAD Magnetron Sputtered Ultra-Thin Copper Oxide Films for Gas-Sensing Application

Abstract: Copper oxide (CuO) ultra-thin films were obtained using magnetron sputtering technology with glancing angle deposition technique (GLAD) in a reactive mode by sputtering copper target in pure argon. The substrate tilt angle varied from 45 to 85° and 0°, and the sample rotation at a speed of 20 rpm was stabilized by the GLAD manipulator. After deposition, the films were annealed at 400 °C/4 h in air. The CuO ultra-thin film structure, morphology, and optical properties were assessed by X-ray diffraction (XRD), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…The copper oxide thin films were deposited in the same DC MF (direct current medium frequency) mode as tin oxide (Cu target purity 4 N—99.99%), and under the same pressure and gas-mixture condition (purity of gases 5 N—99.999%), which are different in comparison with those previously reported [ 37 , 46 ]. However, thanks to the previous experiments with Emission Optical Spectroscopy [ 47 ], the reactive atmosphere can be controlled to provide stable and repeatable conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The copper oxide thin films were deposited in the same DC MF (direct current medium frequency) mode as tin oxide (Cu target purity 4 N—99.99%), and under the same pressure and gas-mixture condition (purity of gases 5 N—99.999%), which are different in comparison with those previously reported [ 37 , 46 ]. However, thanks to the previous experiments with Emission Optical Spectroscopy [ 47 ], the reactive atmosphere can be controlled to provide stable and repeatable conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the most popular resistance sensors are metal oxide semiconductor sensors (MOX) [ 13 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Various metal oxides are used as gas sensors; for example, barium titanate, strontium titanate and barium strontium titanate doped with various elements depending on the doped materials; they behave as p-type or n-type [ 31 , 32 ], n-type including zinc oxide (ZnO) [ 33 , 34 ], tin dioxide (SnO 2 ) [ 35 ], tungsten trioxide (WO 3 ) [ 36 ], indium oxide (In 2 O 3 ), gallium oxide (Ga 2 O 3 ), vanadium oxide (V 2 O 5 ) and iron oxide (Fe 2 O 3 ) and p-type metal oxides such as nickel oxide (NiO), copper oxide (CuO) [ 37 ], cobalt oxide (Co 3 O 4 ), manganese oxide (Mn 3 O 4 ) and chromium oxide (Cr 2 O 3 ) [ 38 , 39 ]. As gas-sensitive materials in gas sensors, heterostructures are also used, such as tin sulfide/tin oxide (SnS 2 /SnO 2 ), tungsten disulfide/titanium dioxide (WS 2 /TiO 2 ), molybdenum disulfide/tin oxide (MoS 2 /SnO 2 ), molybdenum disulfide/zinc oxide (MoS 2 /ZnO), reduced graphene oxide/tin oxide (rGO/SnO 2 ), reduced graphene oxide/carbon dot (rGO/CD), reduced graphene oxide/molybdenum disulfide (rGO/MoS 2 ) [ 40 ], reduced graphene oxide/iron oxide (rGO/F 2 O 3 ) [ 41 ], cobalt tetroxide/titanium dioxide (Co 3 O 4 /TiO 2 ) [ 42 ], zinc oxide/indium oxide (ZnO/In 2 O 3 ), tin oxide/cupric oxide (SnO 2 /CuO), titanium dioxide/vanadium pentoxide (TiO 2 /V 2 O 5 ) [ 30 ], graphene in combination with metal oxides [ 43 ] and many others.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, copper oxide has become increasingly attractive. The copper oxide is a typical p-type semiconductor, it has been used as a base material for several applications, including solar energy cells [7], optoelectronics [8], catalysis [9,10], biosensors [11], supercapacitors [12], lithium ion batteries [13], electrochemical sensors [14], and gas sensors [15]. An actual review of CuO-based gas sensors was presented by the authors of [16], where various different deposition methods, target gases, and operating conditions were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the materials and techniques chosen for the manufacture of coatings, the deposition geometry is also an important factor. The description of production of films by means of Glancing Angle Depostion (GLAD) is extense in literature (ROBBIE; BRETT, 1997;ROBBIE, 1998;SIT et al, 1999;GONZALEZ-ELIPE, AGUSTIN R.;ABADIAS et al, 2019;RYDOSZ et al, 2020). In this type of deposition, the substrate is placed at an oblique angle in relation to the sputtering target, so that the flux of arriving species is off-normal with relation to the substrate surface (BARRANCO; BORRAS; GONZALEZ-ELIPE, AGUSTIN R.;.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…If the substrate is spun around its normal axis the columnar shape of the grains can be changed to a variety of sculptured formats e.g., helix, zig-zag, etc (BARRANCO; BORRAS; GONZALEZ-ELIPE, AGUSTIN R.;. Several authors reported changes in properties related to these grains sculptures that suggest applications in fields as optics, electronics and chemical catalysis (HAWKEYE;BRETT, 2007;LEONTYEV et al, 2008;MANSOUR et al, 2010;RYDOSZ et al, 2020).…”
Section: Mechanical Propertiesmentioning
confidence: 99%